Noninvasive Ventilation in Cardiosurgical Patients with Acute Respiratory Distress Syndrome - A. Ye. Bautin; G. G. Khubulava; A. B. Naumov; V. V. Osovskikh (Общая реаниматология, 2007)
Objective: to evaluate the efficiency of the combined use of traditional respiratory support and noninvasive ventilation (NV) in the therapy of acute respiratory distress syndrome (ARDS) after cardiosurgical interventions. Subjects and materials. The study included 31 patients. The basis for ARDS therapy was respiratory support that met with the principles of safe artificial ventilation (AV); a natural surfactant was endobronchially administered in all cases. The condition for study continuation and randomization was the achievement of the oxygenation index (PaO2/FiO2) up to 200 during assisted ventilation (AV) in the pressure support (PS) + continuous positive airway pressure (CPAP) mode. After simple randomization, the study group patients (n=16) underwent extubation, followed by transfer for NV. Traditional assisted PS+CPAP ventilation was continued in the control group patients (n=15). Results. In both study and control groups, adequate gas exchange, central hemodynamic, and oxygen delivery values could be maintained at all stages of the study. The duration of traditional AV/AV was significantly higher in the control group (128.9±22.4 versus 67.6±12.5 hours; p<0.01). In the study group, retransfer for AV was required in 3 cases (reintubation rate 18.8%). In the control group, 13 (86.7%) patients were transferred for spontaneous respiration); however, 3 patients were further intubated again (reintubation rate 23.1%). In this group, there were 4 (26.6%) cases of ventilator-associated pneumonia; in the study group, infectious complications were absent. Transfer for NV promoted a reduction in the time of treatment in an intensive care unit (152.3±16.5 versus 185.6±10.1 hours in the control group; p<0.01). The study revealed no significant differences in mortality rates (18.8 and 33.3% in the study and control groups, respectively; p<0.05), which is likely to be associated with a small number of observations. Conclusion. The use of NV as a component of respiratory support in ARDS in patients after cardiac intervention makes it possible to maintain adequate gas exchange and tissue oxygen transport, to reduce the frequency and severity complications due to respiratory support and the length of stay in an intensive care unit. NV does not increase the rate of tracheal intubation. Key words: acute respiratory distress syndrome, respiratory support, noninvasive ventilation.